Didactic Possibilities of Using Didactic Methods and Multimedia in Organizing Lesson Processes in Primary Class Students - Robiya Muhiddinova; Sayyora Tilavova (Euro Asian Journal Publishing, 2024)
This article aims to equip elementary school students with knowledge, skills and abilities provided through nature lessons, to effectively use educational methods, interactive methods and tools, and multimedia tools during lessons to create positive feelings that are supposed to be embodied in a perfect person. it is about achieving.
Keywords: multimedia; communication; educational game